Cor triatriatum dexter with right ventricular hypoplasia: Role of multimodality imaging in decision making. Issue 12 (9th November 2018) - Rao, Sruti; Suntharos, Patcharapong; Najm, Hani; Komarlu, Rukmini
Abstract : Cor Triatriatum Dexter (CTD) is a rare congenital anomaly involving the systemic venous valves. Failure of regression of the right‐sided sinus venosus valve leads to abnormal septation of the right atrium and a variety of right atrial and tricuspid valve obstructive lesions. The presentation can be varied ranging from asymptomatic to persistent neonatal cyanosis. We describe a late diagnosis of CTD in a 10‐month‐old male with persistent hypoxia despite balloon valvuloplasty for mild pulmonic valve stenosis with a large secundum atrial septal defect and a mildly hypoplastic right ventricle.